Climate change in the extension curricularization in Higher Education Institutions (HEIs) - Xabregas, Quézia Fragoso; Brasileiro , Tania Suely Azevedo (Seven Editora, 2023)
Climate change has increasingly worried the world. Official reports (IPCC, 2022)¹ show that the climate crisis becomes more serious with each season. Natural and/or anthropic phenomena provide destruction, catastrophes and irreversible damage to nature and humans. Faced with this reality, because he understands the socio-environmental commitment of heI, and with the regulation of Resolution No. 7 of December 18, 2018, which establishes the Guidelines for Extension in Brazilian Higher Education, the study aims to highlight and analyze the theme of climate change in the curricularization of the extension, and elucidate the responsibility of THEIs in the midst of a possible global climate chaos. The Research is bibliographic and documentary type. (FILHO,2022); (GOMES, 2020); (IMPERATORE; PEDDE, 2016); (REIS,2017); (GOMES;BRASILEIRO; CAEIRO, 2020); (MERENGO; SOUZA, 2021); (CLIMATE-U, 2020) among others, bibliographically support this research, and the current legislation snaantise that deals with the theme. From this perspective, it is expected to contribute to the initial training of future professionals committed to climate issues. DOI:https://doi.org/10.56238/methofocusinterv1-075